Matemática e deficiência visual: o que nos informam as pesquisas realizadas em revistas especializadas com crianças até sete anos de idade entre 2019 e 2023? - Xavier, Ana Cláudia de Araújo (2024)
In the first moments of human history, there were behaviors aimed at the inclusion and exclusion of the disabled, as they still occur today, although in a mild way. According to Silva (1987), the reason for talking about people with disabilities today is not only to make visible what happened in the past, but also to register what happens in the present, all the movement that contemporary society performs in the sense of contributing for a dignified and competent life of these subjects. The general objective of this study is to analyze, in publications that involve visual impairment and mathematics in Early Childhood Education and Elementary School - initial years, their contributions to the process of teaching and learning mathematics. Therefore, to carry out this study, we used Silva (1987) and the authors Pereira and Saraiva (2017) as a reference to deal with the historical process of people with disabilities in humanity; we used the current legislation aimed at inclusive education, from the first moment it is suggested in the Salamanca Declaration (1994); and research by Brandão (2006, 2010 and 2011) and Magalhães (2015) on mathematics learning by visually impaired students. This study was carried out from publications published in the annals of the two largest events promoted by the Brazilian Society of Mathematics Education - SBEM, the National Meeting of Mathematics Education - ENEM and the International Seminar on Research in Mathematics Education - SIPEM, in addition to two magazines directed for the education of people with disabilities, the Revista Brasileira de Educação Especial and the Revista Educação Especial, between the years 2019 and 2023. The methodology chosen was bibliographical research, and the collected data were analyzed following the Content Analysis phases of Bardin (2016). Only five publications were found that contemplated the keywords used in the searches, mathematics and visual impairment, and, Early Childhood Education and/or Elementary Education. In these publications, it was observed that the majority are directed to the specific teaching of mathematical contents for students with visual impairment, while the others are focused on how these subjects acquire mathematical notions. When faced with the total number of publications involving the keywords of this research, we noticed the small number of studies carried out with students with visual impairment, demonstrating that there is a real need to expand research aimed at the stages of Early Childhood Education and Elementary School – early years.